PENGARUH BAURAN PEMASARAN JASA TERHADAP LOYALITAS ANGGOTA KOPERASI SIMPAN PINJAM KARYA MURNI MEDAN - Saragih, Nawary (Jurnal Manajemen dan Bisnis, 2019)
The purpose of this research is to know and analyze the influence of service marketing mix to the loyalty of members of Cooperative save and loans Karya Murni Medan. The benefits of this research is to provide information material to the cooperative management about the influence of service marketing mix to member loyalty. The research population is all members of Cooperative save and loans Karya Murni Medan in 2017 as much as 7200 people. The sample of research was 96 respondents with maximum sampling error technique. Required data are collected through questionnaire results. Data analysis technique used is multiple linear regressionanalysis. From the research results obtained correlation coefficient (R) of 0.936 means there is a positive and significant relationship between service marketing mix to member loyalty. Determinant coefficient value (R Square) of 0.875 means loyalty is influenced by service marketing mix factor of 87.5% while the remaining 12.5% again explained by other factors. Multiple linear regression equation obtained from test result Y = 2.589 + 0,488 X1 + 0,214 X2 + 0,270 X3 + 0,180 X4 + 0,105X5 + 0,059X6 + 1,923X7 mean marketing service mix have positive and significant influence to member loyalty.The test results obtained Fcountvalue of 103.159 with the value of sig 0,000 < 0.05 then Hi accepted and H0 rejected, meaning that the marketing service mix significantly influence the loyalty of members at a significant level of 5%. Suggestion by looking at the result of analysis that dominant variable is product variable, promotion and service of consumer need to be maintained by improving execution of service marketing mix conducted in accordance with member desire. While the variables are still smaller effects such as price, place, people / employees, and the process needs to provide uniqueness that is different from other competitors to members more loyal to the purchase of service products offered by the Cooperative